(untitled) (Educational Knowledge, 2024)
Digital competence in the training of future teachers is essential, considering the current context and undoubtedly the future scenario of the new generations that are in constant contact with technologies. The objective of this research is to analyze the level of digital teaching competence in students of pedagogical careers at the Universidad de Los Lagos in Osorno Chile, using the model of the “Common Framework of Digital Teaching Competence” of INTEF1. The methodology followed has been of a mixed, through the application of an online self-perception survey, during the second semester of the year 2022 in which a total of 117 students from various levels of professional pedagogical training at the University participated. The results obtained show a basic level in the areas of Information and Information Literacy; Communication and Collaboration; Creation of digital content, and Security. It is concluded that training in Digital Competencies for future teachers needs to be reconsidered to meet the needs of students in the Chilean school system.